Evaluation of implants with different macrostructures in type I Bone-Pre-Clinical study in rabbits - de Carvalho Silva Leocádio, Amanda [UNESP]; Júnior, Matusalém Silva; de Oliveira, Guilherme José Pimentel Lopes; da Col Santos Pinto, Gustavo [UNESP]; Faeda, Rafael Silveira; Padovan, Luis Eduardo Marques; Júnior, Élcio Marcantonio [UNESP] (MDPI, 2020)
The objective of this study was to assess the primary stability and the osseointegration process in implants with different macrostructures (Cylindrical vs. Hybrid Conical) in rabbit tibiae. Twenty-four (24) rabbits were used, divided into 3 experimental periods (2, 4 and 8 weeks) with 8 animals each. Each animal bilaterally received 2 implants from each group in the tibial metaphysis: Cylindrical Implant (CI) and Hybrid Conical Implant (HCI). All implants were assessed for insertion torque. After the experimental periods, one of the implants in each group was submitted to the removal counter-torque test and descriptive histological analysis while the other implant was used for microtomographic and histometric analysis (%Bone-Implant Contact). HCI implants showed higher insertion torque (32.93 ± 10.61 Ncm vs. 27.99 ± 7.80 Ncm) and higher % of bone-implant contact in the 8-week period (79.08 ± 11.31% vs. 59.72 ± 11.29%) than CI implants. However, CI implants showed higher values of removal counter-torque than HCI implants in the 8-week period (91.05 ± 9.32 Ncm vs. 68.62 ± 13.70 Ncm). There were no differences between groups regarding microtomographic data. It can be concluded that HCI implants showed greater insertion torque and bone-implant contact in relation to CI implants in the period of 8 weeks when installed in cortical bone of rabbits.
Keywords: Dental implants; Macrostructure; Osseointegration